2013
DOI: 10.1155/2013/572729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endothelial Progenitor Cell-Derived Microvesicles on Hypoxia/Reoxygenation-Induced Endothelial Dysfunction and Apoptosis

Abstract: Oxidative stress-induced endothelial dysfunction plays a key role in ischemia/reperfusion injury. Recent evidence indicates that endothelial progenitor cell-derived microvesicles (EPC-MVs) can promote angiogenesis of endothelial cells (ECs). Here, we investigated the potential effects of EPC-MVs on hypoxia/reoxygenation (H/R) injury in human brain microvascular ECs (hb-ECs). MVs were prepared from EPCs cultured in a serum deprivation (SD) medium (starving stress, sEPC-MVs) or SD medium containing tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
130
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 25 publications
7
130
1
Order By: Relevance
“…We found that endothelial progenitor cell-MVs could protect endothelial cells against hypoxia-induced injury in in vitro culture systems [11] . Furthermore, a recent study indicated that MSC-MVs acquire the function of MSCs and can inhibit vascular remodeling and hypoxic pulmonary hypertension in a hypoxia-induced pulmonary hypertension mouse model [12] , indicating a novel application for stem cell-based therapy.…”
Section: Introductionmentioning
confidence: 85%
“…We found that endothelial progenitor cell-MVs could protect endothelial cells against hypoxia-induced injury in in vitro culture systems [11] . Furthermore, a recent study indicated that MSC-MVs acquire the function of MSCs and can inhibit vascular remodeling and hypoxic pulmonary hypertension in a hypoxia-induced pulmonary hypertension mouse model [12] , indicating a novel application for stem cell-based therapy.…”
Section: Introductionmentioning
confidence: 85%
“…EPC-derived microvesicles can protect kidneys from ischemia/reperfusion injury [7] and improve neovascularization in a murine model of hindlimb ischemia through their shuttled microRNAs (miRs), miR-126 and miR-296 [8]. Our group has demonstrated that EPC-released extracellular vesicles could protect ECs against hypoxia/reoxygenation (H/R) injury, which is at least in part mediated by their carried miR-126 [9].…”
Section: Introductionmentioning
confidence: 99%
“…These functional roles might rely on the orchestrated mechanisms associated with MV-carried ribonucleic acids (RNAs) in control of reactive oxygen species (ROS) production and phosphatidylinositol-3 kinase/ endothelial nitric oxide synthase/nitric oxide (PI3K/ eNOS/NO) pathway in the target cells. These findings indicate that EPC-MVs could be used as a novel vehicle for treating H/R injury [50].…”
Section: Mp In Apoptosismentioning
confidence: 76%